MDCM, Inc. (A) : IT strategy synchronization - Jeffery, Mark, 1965-; Yung, Derek; Norton, Joseph F. (London : Kellogg School of Management, 2006)
The case examines the issues of formulating a set of IT objectives aligned with corporate strategy. Specifically, the case describes a firm that has grown rapidly through acquisitions. As a result of these acquisitions, the new conglomerate is not responsive to the competitive environment. The firm has therefore launched a new transformation strategy called Horizon 2000, but it has yet to develop a corresponding IT strategy. Students are then expected to develop an executive-level IT strategy for the firm.
Originally published in Jeffery, M., Yung, D., & Norton, J. F. (2006). MDCM, Inc. (A): IT strategy synchronization. 5-404-770(A). Evanston, IL: Kellogg School of Management at Northwestern University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; MDCM, Inc; Industrial management -- Data processing; Horizon 2000.